A case study in scanner optimisation. (February 2014) - Dudley, NJ; Gibson, NM
Ultrasound scanner preset programmes are factory set or tailored to user requirements. Scanners may, therefore, have different settings for the same application, even on similar equipment in a single department. The aims of this study were: (1) to attempt to match the performance of two scanners, where one was preferred and (2) to assess differences between six scanners used for breast ultrasound within our organisation. The Nottingham Ultrasound Quality Assurance software was used to compare imaging performance. Images of a Gammex RMI 404GS test object were collected from six scanners, using default presets, factory presets and settings matched to a preferred scanner. Resolution, low contrast performance and high contrast performance were measured. The performance of two scanners was successfully matched, where one had been preferred. Default presets varied across the six scanners, three different presets being used. The most used preset differed in settings across the scanners, most notably in the use of different frequency modes. The factory preset was more consistent across the scanners, the main variation being in dynamic range (55–70 dB). Image comparisons showed significant differences, which were reduced or eliminated by adjustment of settings to match a reference scanner. It is possible to match scanner performance using the Nottingham Ultrasound Quality Assurance software as a verification tool. Ultrasound users should be aware that scanners may not behave in a similar fashion, even with apparently equivalent presets. It should be possible to harmonise presets by consensus amongst users.